2010
DOI: 10.1111/j.1468-2435.2009.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Seek Asylum? The Roles of Integration and Financial Support

Abstract: The suspicion that asylum seekers seek beneficial conditions in host areas has become a controversial and popular topic. It has led to accusations of economic migration, with deterrent and preventative measures introduced to try to control this ''problem'', and in particular, the intended uniformity of asylum procedures has been a key aim of European harmonisation talks. As a small, qualitative study, this article is based upon thirteen semistructured interviews held with Somali individuals who sought asylum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The fact that all sought to have homes, work (incomes) and safety at home or in exile (see also Zimmermann, 2010), and that these outcomes were so closely bound with safety/danger, serves to reinforce the challenge that these cases pose to the social constructions or knowledge in this area. Connections existed between 'bogus' and 'genuine' refugee issues, or between different forms of survival including and beyond those that are most typically held to belong to genuine refugees.…”
mentioning
confidence: 88%
“…The fact that all sought to have homes, work (incomes) and safety at home or in exile (see also Zimmermann, 2010), and that these outcomes were so closely bound with safety/danger, serves to reinforce the challenge that these cases pose to the social constructions or knowledge in this area. Connections existed between 'bogus' and 'genuine' refugee issues, or between different forms of survival including and beyond those that are most typically held to belong to genuine refugees.…”
mentioning
confidence: 88%
“…Such exclusion may force refugees to engage in the informal labour sector (Valenta & Thorshaug 2012) or to become dependent on state welfare or community sector support (Zimmermann 2009). Studies have found that refugees do not generally enter host countries with the intention of accessing welfare support -most want to gain employment (Phillimore & Goodson 2006;Valtonen 1998;Zimmerman 2009).…”
Section: Non-legal Barriers To Finding Employmentmentioning
confidence: 99%
“…Choices regarding destinations are often limited for asylum seekers and determined not by personal choices regarding quality of life or ideals but much more by the practicalities and demands of the situation faced (see also Zimmermann, 2009b). Research among Somalis, for example, shows that the Netherlands had often not been a destination they really planned for; they just ‘ended up’ there by coincidence (see also Moret and van Eck, 2006; van Liempt, 2007).…”
Section: Interruptions In Earlier Mobility and The Netherlands As A Cmentioning
confidence: 99%